2000
DOI: 10.1002/(sici)1097-0347(200005)22:3<257::aid-hed8>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin as a local growth promoter in patients with locally advanced tongue cancer: GCRI experience

Abstract: Background The purpose of this study was to assess the role of prolactin (PRL) in men with locally advanced tongue cancer. Methods Circulating PRL was assayed immunoradiometrically in pretherapeutic and sequential blood samples of 99 patients with locally advanced tongue cancer. Patients were followed for 3 years or until their death within a stipulated time. Immunohistochemical localization of PRL was performed on formalin‐fixed paraffin‐embedded tissue sections. Tumoral prolactin receptors (PRLR) were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…In thirteen studies, the potential of salivary and blood biomarkers in tongue cancer was evaluated (Table 1). Five of these papers assessed the performance of 14 different markers for early diagnosis, 19–23 seven assessed performance for prognosis, 2430 while the final study, dealing on pro-inflammatory cytokines, assessed both diagnostic and prognostic performance. 31 Within the included studies, the most promising biomarkers were IL-6 and IL-8 that showed consistent evidence for clinical usefulness in detection and diagnosis, and prolactin in prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…In thirteen studies, the potential of salivary and blood biomarkers in tongue cancer was evaluated (Table 1). Five of these papers assessed the performance of 14 different markers for early diagnosis, 19–23 seven assessed performance for prognosis, 2430 while the final study, dealing on pro-inflammatory cytokines, assessed both diagnostic and prognostic performance. 31 Within the included studies, the most promising biomarkers were IL-6 and IL-8 that showed consistent evidence for clinical usefulness in detection and diagnosis, and prolactin in prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular mechanisms underlying this result have yet to be clarified. Bhatavdekar et al (2000) detected hPRL protein and mRNA expression in 44 and 85% of SCCHN patients, respectively, and proposed a role for hPRL as a local growth promoter. However, there is currently no study available that investigates the influence of hPRL on the growth of SCCHN cancer cells generated from primary tumours and their corresponding metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In the second study, PRLR measured by a ligand binding assay and by PRLR mRNA using RT–PCR were detectable in 8 out of 24 (33%) and 41 out of 50 (82%) of tumour samples, respectively. However, follow-up data, including clinical outcome, were not available in that investigation (Bhatavdekar et al , 2000). Our study shows for the first time that in a large cohort of patients, PRLR expression in tumour tissues is significantly associated with a decreased survival in SCCHN patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In specific, there was an increased risk of upper and lower gastrointestinal cancer, with a higher risk among women than men. Other studies have reported higher prolactin levels among persons with several cancer types [36][37][38][39][40], including hepatocellular carcinoma, the dominant histological type of liver cancer [41][42][43][44]. In these cross-sectional studies, serum prolactin levels, or protein expression of prolactin in tissue samples, were significantly higher in hepatocellular carcinoma cases than in controls [41][42][43][44].…”
Section: Discussionmentioning
confidence: 95%